Method of forming of readiness of social teachers to work with gifted children. (Journal of Educational Sciences, 2016)
As the analysis of the modern pedagogical practice, a large number of young social workers are currently experiencing difficulties in social and educational work with gifted children. Our analysis of the studies on the socio- training of teachers in higher education institutions of the Republic of Kazakhstan to the profession suggests that modern trainingof social workers are not fully focused on work with gifted children. This is , of course, complicates the process of social adaptation of young teachers to the profession with gifted children in educational institutions, to work with families who have children in this category , as well as to work with subject teachers . For effective social and educational work with gifted children have social educator, in our opinion, is to be formed is appropriate readiness. Begin to shape a willingness to work with gifted children have social educator must still within the walls of the university, in order tocome to an educational institution , the specialist has already been «armed» knowledge and skills necessary and carried out its activities clearly work out a procedure . In our opinion, help in the formation of readiness to work with gifted children can appropriate technique. While working on the master’s thesis on the topic: «Psycho- pedagogical conditions of formation of readiness of the social teacher to work with gifted children,” we have proposed a variant methodology to efficiently generate social willingness of teachers to work with gifted children.
Keywords: social teacher; gifted children; readiness of social teacher; method of forming; forming of readiness